Narrative and Expository Writing of Adolescents With Language-Learning Disabilities: A Pilot Study. (May 2013) - Hall-Mills, Shannon; Apel, Kenn
We evaluated the narrative and expository writing samples of 12 adolescents with language-learning disabilities (LLD) in Grades 6 to 12 for elements of microstructure (e.g., productivity, grammatical complexity) and macrostructure (genre-specific text structure elements) using an experimental measure. Writing samples were elicited with genre-specific prompts via paper and pencil and transcribed according to Systematic Analysis of Language Transcripts (SALT) conventions. Wilcoxon signed ranks tests indicate that levels of productivity and grammatical complexity were significantly greater in the narrative genre than in the expository genre. However, participants' writing samples demonstrated equally impoverished text structure for both genres. Positive correlations were found between microstructure and macrostructure performance. Findings confirm the effects of discourse genre on measures of microstructure and further elucidate the use of microstructure and macrostructure elements in the writing of adolescents with LLD. Future research, comprehensive writing assessment, and interventionists should consider direct measurement of both microstructure and macrostructure components across genres for this population.